Analisis Pengelolaan Persediaan dan Distribusi Container di Depo Container - Pertiwi, Dewi Cahya; Sahara, Siti (Sahabat Publikasi, 2023)
Ports are the main key in export and import trade activities, but ports in carrying out their functions are assisted by several sectors that influence each other. Then this regard, depots have a significant role in supporting the smooth distribution of the flow of goods at the port because container depots are located in strategic places close to the port to speed up the shipping process. With the continued rapid development of technology, it has a positive impact on the development of transportation because it is in line with the increasing human need to send goods practically, efficiently and safely from all weather conditions, therefore there are often many internal and external obstacles that influence inventory management and container distribution. at the depot, in this case this research will discuss problems at the depot and the strategic analysis that will be achieved in these problems, which is expected to optimize the management of inventory and distribution of containers at the depot.